Differential effects of FTY720 on the B cell compartment in a mouse model of multiple sclerosis - Bail, Kathrin; Notz, Quirin; Rovituso, Damiano M.; Schampel, Andrea; Wunsch, Marie; Koeniger, Tobias; Schropp, Verena; Bharti, Richa; Scholz, Claus-Juergen; Foerstner, Konrad U.; Kleinschnitz, Christoph; Kuerten, Stefanie (Journal of Neuroinflammation, 2017)
BACKGROUND: MP4-induced experimental autoimmune encephalomyelitis (EAE) is a mouse model of multiple sclerosis (MS), which enables targeted research on B cells, currently much discussed protagonists in MS pathogenesis. Here, we used this model to study the impact of the S1P1 receptor modulator FTY720 (fingolimod) on the autoreactive B cell and antibody response both in the periphery and the central nervous system (CNS). METHODS: MP4-immunized mice were treated orally with FTY720 for 30 days at the peak of disease or 50 days after EAE onset. The subsequent disease course was monitored and the MP4-specific B cell/antibody response was measured by ELISPOT and ELISA. RNA sequencing was performed to determine any effects on B cell-relevant gene expression. S1P1 receptor expression by peripheral T and B cells, B cell subset distribution in the spleen and B cell infiltration into the CNS were studied by flow cytometry. The formation of B cell aggregates and of tertiary lymphoid organs (TLOs) was evaluated by histology and immunohistochemistry. Potential direct effects of FTY720 on B cell aggregation were studied in vitro. RESULTS: FTY720 significantly attenuated clinical EAE when treatment was initiated at the peak of EAE. While there was a significant reduction in the number of T cells in the blood after FTY720 treatment, B cells were only slightly diminished. Yet, there was evidence for the modulation of B cell receptor-mediated signaling upon FTY720 treatment. In addition, we detected a significant increase in the percentage of B220+ B cells in the spleen both in acute and chronic EAE. Whereas acute treatment completely abrogated B cell aggregate formation in the CNS, the numbers of infiltrating B cells and plasma cells were comparable between vehicle- and FTY720-treated mice. In addition, there was no effect on already developed aggregates in chronic EAE. In vitro B cell aggregation assays suggested the absence of a direct effect of FTY720 on B cell aggregation. However, FTY720 impacted the evolution of B cell aggregates into TLOs. CONCLUSIONS: The data suggest differential effects of FTY720 on the B cell compartment in MP4-induced EAE.
EVALuna2:35216